2018
DOI: 10.1002/adsc.201800409
|View full text |Cite
|
Sign up to set email alerts
|

A recyclable Ru(CO)Cl(H)(PPh3)3/PEG catalytic system for regio‐ and stereoselective hydroboration of terminal and internal alkynes

Abstract: This paper reports on the first repetitive batch selective hydroboration of terminal and internal alkynes in a series of poly(ethylene glycols) (PEGs), used as solvents and media for the immobilization of a Ru(CO)Cl(H)(PPh3)3 catalyst. The system based on 2 mol% of Ru−H complex and poly(ethylene glycol) with α‐methyl/ω‐trimethylsilyl ending groups (Mw=2000) was found to be the most efficient, and was able to carry out over 19 complete runs with the Z‐addition of pinacolborane to the phenylacetylene. With the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…In the related reports, the heterogeneous catalysts used are mainly nanocatalysts, polymer, and disordered metal@polymers [10b,16] . However, some limitations such as only one alkyne substrate, [16a,c] low yield of alkyl alkynes, [10b] and limited selectivity are encountered [16b] . The development of new type of applicable heterogeneous catalysts with defined structural features (open metal sites and/or heterogeneous carriers) is important for the selective hydroboration of alkynes with high yield, high selectivity, and wide range of substrates.…”
Section: Methodsmentioning
confidence: 99%
“…In the related reports, the heterogeneous catalysts used are mainly nanocatalysts, polymer, and disordered metal@polymers [10b,16] . However, some limitations such as only one alkyne substrate, [16a,c] low yield of alkyl alkynes, [10b] and limited selectivity are encountered [16b] . The development of new type of applicable heterogeneous catalysts with defined structural features (open metal sites and/or heterogeneous carriers) is important for the selective hydroboration of alkynes with high yield, high selectivity, and wide range of substrates.…”
Section: Methodsmentioning
confidence: 99%
“…These reactions were quite selective for cis -hydroboration, though conversions were often not quantitative and reusing the catalyst led to a decrease in activity. 371 Separate studies have looked specifically at ruthenium catalysts in ionic liquids (with or without supercritical CO 2 ), 372 in supercritical CO 2 , 373 or in polyethylene glycol, 374 finding good selectivity through multiple catalytic cycles.…”
Section: Scopementioning
confidence: 99%
“…Compound 28 has previously been described as an active catalyst in hydroboration of terminal-or internal monoalkynes in conventional and novel, green reaction media (supercritical CO 2 (scCO 2 ), ionic liquids (ILs), polyethylene glycol, (PEG)). 72,75,76,128,129 The reaction proceeded effectively for various diynes possessing electron-withdrawing or electron-donating substituents on the aryl ring, as well as for heterocyclic 1,4-di(thiophen-3-yl)buta-1,3-diyne 27c. Alkyl-substituted diynes yielded boryl-substituted enynes by cis-addition of borane to the CRC bond, but the postreaction mixture also consisted of other monoborylated enynes, bisborylfunctionalised dienes, and some undefined products.…”
Section: Hydroboration Of Conjugated 13-diynesmentioning
confidence: 99%
“…[63][64][65][66][67][68][69][70][71] Working on the hydroboration and hydrosilylation of various unsaturated compounds and especially on the reactivity of conjugated 1,3-diynes in these processes, we have found that literature information is often scattered, with no detailed procedures or much discussion on the process optimisation or methodology. [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] Therefore, we have decided to build a comprehensive and critical compendium focused on this subject, which will systemise the existing knowledge on the hydroelementation of diynes in relation to the formation of different products. We will also show the possible applications of the obtained products in the synthesis of fine chemicals and materials.…”
Section: Introductionmentioning
confidence: 99%